EXPLOITING PROJECT-BASED LEARNING APPROACHES TO FOSTER GLOBAL CITIZENSHIP EDUCATION IN LOWER SECONDARY CIVIC EDUCATION - Thi Thu Ha, Luu; Thi Thoa, Doan (HNUE Journal of Science: Journal of Educational Science, 2025)
In the context of increasing global interdependence and social complexities, Global Citizenship Education (GCED) has emerged as an essential educational orientation aimed at equipping learners with knowledge, skills, attitudes, and values necessary to engage actively and responsibly with global issues. Given its intrinsic connection to the formation of civic consciousness and social responsibility, Civic Education provides a suitable context for the integration of GCED content and competencies. Using document analysis, this study explores the project-based learning approach as an effective pedagogical strategy for promoting global citizenship education at lower secondary level. The paper focuses on proposing a process for designing project-based learning activities for GCED in Civic Education, emphasizing the alignment between learning objectives, interdisciplinarity, student agency, and the practical relevance of learning activities.